2000
DOI: 10.1007/s002770000159
|View full text |Cite
|
Sign up to set email alerts
|

Culture requirements for induction of dendritic cell differentiation in acute myeloid leukemia

Abstract: A substantial fraction of the genome is transcribed in a cell-type-specific manner, producing long non-coding RNAs (lncRNAs), rather than protein-coding transcripts. Here, we systematically characterize transcriptional dynamics during hematopoiesis and in hematological malignancies. Our analysis of annotated and de novo assembled lncRNAs showed many are regulated during differentiation and mis-regulated in disease. We assessed lncRNA function via an in vivo RNAi screen in a model of acute myeloid leukemia. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Thus, in agreement with other groups, we found that upregulation of CD80 expression on AML cells by gene transfer 29 and exposure of AML to GM-CSF 23,24 can both lead to T cell stimulatory responses, which can be combined by lentiviral gene transfer of both genes.…”
Section: Increased Auto-stimulatory Activity Of Aml Cells Expressing supporting
confidence: 75%
See 1 more Smart Citation
“…Thus, in agreement with other groups, we found that upregulation of CD80 expression on AML cells by gene transfer 29 and exposure of AML to GM-CSF 23,24 can both lead to T cell stimulatory responses, which can be combined by lentiviral gene transfer of both genes.…”
Section: Increased Auto-stimulatory Activity Of Aml Cells Expressing supporting
confidence: 75%
“…21 In particular, since GM-CSF and interleukin-4 (IL-4) are key in obtaining monocytederived DC cultures in vitro, 22 the strategy to drive AML cells into DC differentiation ('AML-DC') in the presence of recombinant GM-CSF and IL-4 has been studied with variable but overall successful results. [23][24][25][26] It has been shown previously that autocrine stimulation after retroviral vector gene transfer of GM-CSF into multipotent murine stem cell lines (FDCP mix) induced their synchronous maturation, driving differentiation into granulocytes and macrophages. 27 To our knowledge, however, this is the first demonstration of a maturation effect in primary human AML cells after GM-CSF gene transfer.…”
Section: Transduction Of Primary Aml Cells Is Stable and Continuous Ementioning
confidence: 99%
“…It is of interest to note that recent studies [44][45][46] have provided evidence that APL blasts also possess the capacity to differentiate to functional dendritic cells. This finding is fully compatible with our observations and it is tempting to suggest that the APL blasts differentiating to dendritic cells under appropriate culture conditions (ie in the presence of GM-CSF, IL-4 and Leukemia TNF-␣), represent the same population able to mature to monocytic cells also under the culture conditions here reported.…”
Section: Discussionmentioning
confidence: 99%
“…The AML French-AmericanBritish classification (FAB) subtype does not appear to predict DLLC differentiation potential as leukaemia cells from all FAB subtypes have been shown to undergo DLLC differentiation. [1][2][3][4][5][6][7][8][9] A more significant determinant may be the cytogenetic/ molecular rearrangement underlying the individual cases of AML. Several lines of evidence point towards a common theme in the molecular pathogenesis of AML, namely that the end result of the majority of the commonest chromosomal translocations is the transcriptional repression of genes involved in haematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…These DLLC share many features in common with monocyte-derived dendritic cells (MDDC) in that they express the costimulatory molecules CD40, CD80 and CD86 and the dendritic cell-associated molecule CD83, [1][2][3][4][5][6][7][8][9] secrete the immunostimulatory cytokine IL-12 3 and are potent stimulators of allogeneic T lymphocytes in mixed leukaemia lymphocyte reactions (MLLR). [1][2][3][4][5][6]9 Importantly, it has been demonstrated that autologous cytotoxic T lymphocytes, capable of recognising and destroying unmodified leukaemia cells, can be generated by co-culturing T cells with autologous DLLC.…”
Section: Introductionmentioning
confidence: 99%